Legal Analysis of Legal Protection for New Creditors (Cessionaries) Related to Obligation Recording on the Mortgage Certificate for Transfer Receivables (Cessie) When the Debtor Defaults - Hutomo, Putra; Andreawan, Jose (Journal Evidence Of Law, 2025)
Study This aim For analyze base laws, procedures and implications juridical obligation recording diversion receivables on certificates right liability as form protection law for creditors new, and study consequence law if recording the No done before debtor default. The research method used is study juridical normative with approach legislation, approach conceptual approach​ analytical and approach case. Data sources obtained through studies literature to regulation legislation, doctrine law, as well as decision court related dispute right liability and transfer receivables. Research results show that recording transition right creditors in certificate right liability is instrument law of a legal nature constitutive For ensure certainty law and publication to party third. Without recording, creditors new No own legitimacy full For execute object right liability, so that cause risk disappearance priority rights and potential lost in dispute with other creditors or buyer good faith auction good. Therefore tha, protection law for creditors new must realized through obligation recording that is done quick after diversion receivables, as well as strengthening arrangement in UUHT for anticipate potential default debtors in the middle of the transition process.